A review of entomopathogenic nematodes as a biological control agent for red palm weevil, Rhynchophorus ferrugineus (Coleoptera: Curculionidae) - Khairuddin, Wan Nurashikin; Abdul Hamid, Siti Noor Aishikin; Mansor, Mohammad Saiful; Bharudin, Izwan; Othman, Zulkefley; Jalinas, Johari (MDPI, 2022)
Rhynchophorus ferrugineus (Olivier) (Coleoptera: Curculionidae) is a severe pest of palm trees worldwide. The development and feeding activities of R. ferrugineus larvae inside the trunk damage palm trees. However, the absence of noticeable infestation signs at an early stage contributes to the spread of the attack. Integrated pest management (IPM) has been introduced to control R. ferrugineus infestation by implementing various approaches and techniques. The application of chemical pesticides has shown impressive results. However, biological control should be applied as an alternative solution due to adverse environmental impacts and pest resistance issues. One example is the use of entomopathogenic nematodes (EPNs) as biological control agents, which can forage and attack targeted pests without compromising the environment and other nontarget organisms. EPNs and their symbiotic bacteria have a mutualistic interaction that can kill the host within a short period of time. Therefore, this review emphasizes the effectiveness of entomopathogenic nematodes and their symbiotic bacteria against R. ferrugineus.